PEMANFAATAN METODE ROLE PLAYING DALAM MENINGKATKAN PEMAHAMAN SISWA TERHADAP PERISTIWA SEJARAH - Yonggom, Aplonia; Ayomi, Golden Ringgo (NOKEN : Jurnal Pengelolaan Pendidikan, 2023)
Historical material in teaching and learning activities in schools is often considered the most boring because it contains past facts. This is sometimes not realized by the subject teacher. The boring thing lies in the role of the teacher who prepares and teaches it. Because the output of teaching and learning activities experienced by students is an essential understanding, and positive values; nationalism, and patriotism can be practiced in social life. The purpose of this research is to provide understanding to teachers as well as students that the use of the role playing method is considered important to change the mindset that history lessons are boring. Because in its application it requires cooperation and inspiration for the role played. So it is hoped that the values and attitudes of patriotism and nationalism will become stronger in the souls of students and the younger generation of Indonesia in general. The results of this study have provided an understanding of the learning actors; The teacher said that the role playing learning method is an appropriate alternative method in teaching history subjects. Thus, history subjects which are loaded with events or incidents, places, and times will be more meaningful if the flashbacks in the learning activities are carried out through role playing; imitating the characters in the story, recreating the atmosphere and place of events or events.